Cuban flute style : interpretation and improvisation - Miller, Sue, 1966- (Scarecrow Press, 2014)
In Cuban Flute Style: Interpretation and Improvisation, Sue Miller-music historian, charanga flute player, and former student of Richard Egües-examines the early-twentieth-century decorative style of flute playing in the Cuban danzón and its links with the later soloistic style of the 1950s as exemplified by Fajardo and Egües. Transcriptions and analyses of recorded performances demonstrate the characteristic elements of the style as well as the styles of individual players.